Funktionen populärer Fantasy-Literatur in der christlichen Rezeption - Gebbe, Hans-Christian (Universitätsverlag Göttingen, 2017)
Daily devotionals exploring spiritual themes in Harry Potter, youth pastors giving sermons wearing Jedi robes, missionary groups using Bilbo's journey to share the Gospel of Christ: There is apparently a high level of interest within the Christian community to engage with popular culture. This applies in particular to fictional works dealing with the supernatural or fantastic otherworlds. The aim of this study is to show how fantasy literature can be used in modern society to articulate religious themes. The focus lies on Christian literature such as devotional books and didactic resources for ministry addressing Christian readers in Germany, the United Kingdom and the United States of America. By analysing Christian literature reflecting Harry Potter, His Dark Materials and Left Behind (works of fantasy that strongly differ in their engagement with religious themes) this thesis shows how Christian teachers, apologists, writers and speakers create biblical analogies and use (religious) archetypes to build a bridge between the narratives of popular culture, Christian tradition and the reader's personal story.